The Impact of Service Orientation and Airport Service Quality on Passenger Satisfaction and Image: Evidence from Indonesia - Agus Usman; Yudi Azis; Budi Harsanto; Anton Mulyono Azis (Logistics)
Background: Airport service quality and service orientation are important aspects of managing passenger satisfaction and airport image. The aim of this paper is to analyze the influence of service orientation and airport service quality on airport image through passenger satisfaction as an intervention variable. Methods: The survey was conducted on 356 passengers at the departure area and lounge. Samples were taken at five major airports in Indonesia, including Soekarno Hatta International Airport. To test the influence of exogenous variables on endogenous variables through intervening variables, a quantitative testing analysis test was carried out using the structural equation model partial least square (SEM-PLS). Result: The research results show that service orientation has a significant and positive effect on airport service quality, passenger satisfaction, and airport image. Moreover, service quality also has a positive effect on passenger satisfaction and the airport’s image. Empirically, passenger satisfaction has been proven to mediate the influence of service quality and service orientation on airport image. It has been proven that airport operators who focus on passengers through service orientation can increase passenger satisfaction and the airport’s image. Conclusions: Focusing on passengers’ needs while at the airport is an important aspect for airport operators who aim to manage their emotions, which encourages passengers to use paid services while in the waiting room. The use of this paid service will directly increase the airport’s aeronautical revenue. Future research needs to consider the influence of image on purchase intention and return to the airport.